STUDI KOMPARATIF IMPLEMENTASI AJARAN TRI KAYA PARISUDHA DI LINGKUNGAN KELUARGA DAN SEKOLAH - Sefira, Galoh Fresti (UHN IGB Sugriwa Denpasar, 2026)
Character education is an important aspect in shaping a generation with noble morals. In Hinduism, Tri Kaya Parisudha, the purity of thought, speech, and action, serves as a relevant moral guideline. This study aims to comparatively analyze the implementation of Tri Kaya Parisudha teachings in schools and families. The method used was qualitative with a literature review, in-depth interviews, and participant observation. The results show that the implementation of Tri Kaya Parisudha in schools is more structured through the curriculum and extracurricular activities, while in families it is more through role models and habits. The main supporting factor is the synergy between teachers and parents, while the main obstacle is the lack of in-depth understanding outside the ritual context. It is concluded that collaboration between schools and families is crucial to ensure consistent character formation based on Tri Kaya Parisudha.